Pengaruh Model Pembelajaran Radec Terhadap Keterampilan Menulis Teks Cerpen Siswa Kelas VIII SMPN 7 Padang - Rahmadhani, Dwi Putri; Zuve, Farel Olva; Rasyid, Yulianti; Ningsih, Ayu Gustia (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF THE RADEC LEARNING MODEL ON WRITING SKILLS OF SHORT STORY TEXTS OF GRADE VIII STUDENTS OF SMPN 7 PADANG This study aims to determine the effect of the RADEC (Read–Answer–Discuss–Explain–Create) learning model on the short story writing skills of eighth-grade students of SMPN 7 Padang. Short story writing skills are an important part of learning Indonesian that requires mastery of the structure, elements, and linguistic features. This study uses a quantitative method with a pretest-posttest control group design. The research sample consisted of two randomly selected classes, namely the experimental class using the RADEC model and the control class using the conventional learning model. The research instrument was a short story writing test that was analyzed based on the structure, intrinsic elements, and linguistic features of the short story text. The results of the study indicate that there is a positive effect of the application of the RADEC model on students' short story writing skills. The RADEC model helps students understand the steps of writing systematically and improves the quality of their writing. Thus, the RADEC model is effective for use in learning to write short stories.